2020
DOI: 10.1007/s11126-020-09847-x
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability and Feasibility of Using Text Messaging to Support the Delivery of Physical Health Care in those Suffering from a Psychotic Disorder: a Review of the Literature

Abstract: Those suffering with serious mental illness (SMI), such as psychotic disorders, experience life expectancy 15 years shorter than the general population. Cardiovascular disease is the biggest cause of death in those with psychotic disease and many risk factors may be limited by healthy lifestyle choices. Text messaging interventions represent mobile health (mHealth), a nascent way to deliver physical health care to those suffering with a psychotic disorder. This paper aims to review the literature on the feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A key strength of SMS text messaging is its flexibility, allowing a range of content (within the 160-character limit), including psychoeducation, reminders (eg, to exercise or take medication), motivational messages, self-care (eg, stress management tips), and informative links to health-related internet sites [ 51 ]. The simple language format used in texts also increases their accessibility, irrespective of the reading level [ 52 - 55 ]. The ability to send SMS text messages anonymously may help minimize stigma and barriers to accessing health care [ 56 ], which are particularly evident in geographically isolated underserved populations [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…A key strength of SMS text messaging is its flexibility, allowing a range of content (within the 160-character limit), including psychoeducation, reminders (eg, to exercise or take medication), motivational messages, self-care (eg, stress management tips), and informative links to health-related internet sites [ 51 ]. The simple language format used in texts also increases their accessibility, irrespective of the reading level [ 52 - 55 ]. The ability to send SMS text messages anonymously may help minimize stigma and barriers to accessing health care [ 56 ], which are particularly evident in geographically isolated underserved populations [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…The approach relies on analyzing patterns in language that may be indicative of cognitive, psychological, or even some physical health conditions. Here's how it might work for various conditions, like: (1) Mental health disorders [28,29]: (a) changes in the frequency of communication, use of negative words, and shifts in the complexity of language may suggest depression or anxiety [7]; (b) the disorganized thought patterns that emerge in how a person composes messages could be a warning sign of psychotic disorders [30]; or (c) the repeated questions, simpler sentence structures, or a notable decline in the complexity of language could indicate cognitive decline, like Alzheimer's disease and dementia [4];…”
Section: Introductionmentioning
confidence: 99%
“…mHealth technology (e.g. mobile-phone apps), have reduced sedentary behaviour in individuals with mental-health problems; for example, text message prompts increased step-counts in those with severe mental-health problems ( Chen et al, 2017 ), and a literature-review found that motivational/supportive text messages improved physical health in those with a psychotic disorder ( Griffiths, 2020 ). Although, mHealth app research to reduce sedentary behaviour in those with psychosis is limited, apps are effective in increasing active behaviour in the general population ( Conroy et al, 2014 ; Hollis et al, 2015 ; Vandelanotte et al, 2016 ).…”
mentioning
confidence: 99%